2018
DOI: 10.1186/s13643-018-0886-3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions integrating health and academic interventions to prevent substance use and violence: a systematic review and synthesis of process evaluations

Abstract: BackgroundWithin increasingly constrained school timetables, interventions that integrate academic and health education to reduce substance use and violence may hold promise as a category of intervention that can positively affect both academic and health outcomes. There are no current systematic reviews exploring the effectiveness of such interventions or factors that affect their implementation.MethodsA total of 19 bibliographic databases and 32 websites were searched. References were also extracted from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 42 publications
5
24
0
1
Order By: Relevance
“…More generally, our study provides evidence that schoolbased health interventions must ensure they do not overburden schools, particularly in contexts where school systems are stressed by budgetary or staffing problems and performance pressures (Sturgis, Smith, and Hughes 2006;Han and Weiss 2005). In line with previous research, this study raises concerns that schools struggle to deliver separate interventions for each health issue affecting their students (Tancred et al 2018), and so may be unwilling or unable to deliver an intervention focused solely on dating and relationship violence. Dating and relationship violence might best be addressed as an aspect of comprehensive relationships and sex education as suggested in recent studies (Santelli, Grilo, and Choo et al 2018;Wolfe et al 2009), with there being no clear evidence of a certain minimum dose for intervention effectiveness in reducing dating and relationship violence (Fellmeth, Heffernan, and Nurse et al 2013).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…More generally, our study provides evidence that schoolbased health interventions must ensure they do not overburden schools, particularly in contexts where school systems are stressed by budgetary or staffing problems and performance pressures (Sturgis, Smith, and Hughes 2006;Han and Weiss 2005). In line with previous research, this study raises concerns that schools struggle to deliver separate interventions for each health issue affecting their students (Tancred et al 2018), and so may be unwilling or unable to deliver an intervention focused solely on dating and relationship violence. Dating and relationship violence might best be addressed as an aspect of comprehensive relationships and sex education as suggested in recent studies (Santelli, Grilo, and Choo et al 2018;Wolfe et al 2009), with there being no clear evidence of a certain minimum dose for intervention effectiveness in reducing dating and relationship violence (Fellmeth, Heffernan, and Nurse et al 2013).…”
Section: Resultssupporting
confidence: 80%
“…This suggests a need for prevention targeting those in early and middle adolescence informed by existing evidence. Implementing relationships and sex education and other health interventions in schools is best facilitated by committed school leaders and staff trained and supported to deliver health lessons (Pearson et al 2015;Tancred et al 2018). However, delivering health interventions in schools is challenging because of the limited incentives for schools to address students' health and the lack of training and support available on how to do this (Tancred et al 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, most of the SMs were able to generate and cultivate the support of those teachers who believed in the value of the program and were willing to participate in program activities and this also aided in successful implementation in the SM-led schools. These facilitators are consistent with studies of the implementation of school health interventions [13][14][15]. For example, a process evaluation of the Mentally Healthy Schools program in Australia reported that if the principals and teachers are passionate about the program then that sets the tone positive and supports implementation.…”
Section: Discussionsupporting
confidence: 68%
“…There may be less political incentive to sustain health interventions; academic education is likely to be prioritised [28][29][30]. Teachers may need more support and preparation time to deliver curriculums that include health [31] and vary in their commitment to teaching health promotion [13,31]. Limited interaction between schools and the health sector might impede the identification of funding, resources and training for sustainability [30].…”
Section: Introductionmentioning
confidence: 99%